MACROECONOMIC STABILITY AS A DRIVER OF FOREIGN DIRECT INVESTMENT: LESSONS FROM UZBEKISTAN (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the impact of macroeconomic stability on attracting foreign direct investment (FDI), using Uzbekistan as an example. The paper examines the theoretical aspects of FDI, the types and forms of investment, and the importance of macroeconomic stability as a key factor for long-term investment. It also analyzes the macroeconomic situation in Uzbekistan, including GDP dynamics, inflation, foreign exchange policy, fiscal discipline, and institutional reforms. To complement the conceptual discussion, the study introduces an empirical analysis using recent macroeconomic data for Uzbekistan, providing quantitative evidence on the relationship between macroeconomic stability and FDI inflows.
Keywords: Macroeconomic stability, foreign direct investment (FDI), economic growth, inflation, foreign exchange policy, investment climate, Uzbekistan.